y=-2*1-1

Simple and best practice solution for y=-2*1-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=-2*1-1 equation:


Simplifying
y = -2 * 1 + -1

Multiply -2 * 1
y = -2 + -1

Combine like terms: -2 + -1 = -3
y = -3

Solving
y = -3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -3

See similar equations:

| 2(7+8m)+6=10+6m | | y=-2*0-1 | | 3a=-6 | | -3(z-8)=54 | | -7x-2(-3x-11)=12 | | 0=-5t^2+5t+30 | | 3y-6*2=9 | | 10-3+(6*4)= | | 3.2+(x+5.1)= | | 3.08sqrtx+18.97=2.87sqrtx+20.08 | | 3y-6*1=9 | | 9-2x=3x-8 | | 3y-6*0=9 | | x-0.31x= | | (7x+4)=(3x+6) | | 2x+(45-x)+4x=180 | | 2y-4*2=8 | | -(-2x+4)=16 | | 9+x=27 | | 3x-12+4x+3=180 | | 36x+145=433 | | 7(200)+12x=1125 | | 3(22)=x-4 | | k^2-2k-3=0 | | 2(x-6)=-26 | | log(x+11)15=1 | | 6x+6=7x+1 | | (5+3j)+(4-j)=0 | | 1.5x+2=-5.8x-5 | | 2x+4b=6 | | 3x+33=8x-2 | | 2y-4*1=8 |

Equations solver categories